OBSERVATIONS OM THE PLANKTON OF THE COCHIN BACKWATERS - George, M J (Indian Journal of Fisheries, 2016)
Considerable work, both qualitative and quantitative, has been done onthe plankton of Indian coastal waters in recent years. But the planktonof Indian backwaters has received little attention so far. Sewell (1913,1924 and 1934) has studied plankton, more especially the copepods, of theChilka Lake and the salt lakes of Calcutta. The brackish water fauna ofAdyar backwaters was studied by Panikkar and Aiyar (1937). Chackoetal. (1953, 1954 o, 1954 A and 1954 c) have made brief references to planktonicorganisms also in their studies on the hydrobiology and fisheries ofvarious lakes and estuaries of Madras. A preUminary study of the planktonof the Chilka Lake has been made recently by Devasundaram and Roy(1954).